ANALYSIS OF THE USE OF PRESENT TENSES IN WRITING - I Gusti Agung Vony Purnama (SPHOTA: Jurnal Linguistik dan Sastra, 2017)
ABSTRACT This study aims to find out the common use of present tenses in the students’ writings and the difficulties they faced in using those tenses. The students under concern were the first-semester students of the academic year 2016 taking “English 1” subject at Bali STIKOM Regular Program. This study used the theory of English Grammar and theory of Contrastive Analysis. The English Grammar theory was used to identify and analyze the use of present tenses in the students’ sentences, while the theory of contrastive analysis was used to analyze the students’ difficulties in using those tenses in their writings. The result of the analysis shows that of the 34 student writings under analysis. 77.4% use simple present tense, 10% present perfect tense, 6.9% present continuous tense, and 5.7% present perfect continuous tense. There are some difficulties faced when using the present tenses. The students seem to ignore the function of the adverb as the basis for deciding the proper forms of the verbs to be used. The students also find it difficult to add ‘-s’ or ‘-es’ accordingly to the infinitive verbs to show agreement with the subjects of the sentences being constructed. In addition, they still show lack of understanding of the function of each type of the present tenses. Keywords: Sentence, Present Tenses